“Era stata trovata nello scassare fra certe anticaglie una lapide sepolcrale di marmo con iscrizione”: Le epigrafi antiche e la storia degli Orsini - Di Giovannandrea, Riccardo (Römische Mitteilungen, 2024)
The Orsini, during the 16th century, tried to give shape to a genealogy of their lineage that integrated the Germanic and Roman origins and the key work in this sense was undoubtedly Francesco Sansovino's Historia di Casa Orsina, published in Venice in 1565, but the Barberini Archive preserves further and interesting documentation. When Charles, brother of Pope Urban VIII, decided to purchase Monterotondo, one of the oldest Orsini fiefdoms, information was collected on the history of the selling family, including genealogical manuscripts. One of them appears worthy of note for the presence of some Latin inscriptions, well described and drawn, justifying the antiquity of the family. In this contribution we will try to reconstruct the inventive context of that narrative by following the history of the cited inscriptions and arriving at the identification of the authorship of the manuscript.